Genetic diversity and differentiation of Aquilaria malaccensis Lam. using RAPD markers - Hasan Nudin, Nur Fatihah; Jamali, Nur Anisah; Alias, Nadiawati; Mahmod, Nor Hasima; Mahmud, Khairil; Ali, Abdul Manaf (Innovative Scientific Information & Services Network, 2020)
Aquilaria malaccensis Lam. (family Thymelaeaceae) commonly known as agarwood or gaharu producing tree in Malaysia. The tree is being heavily exploited due to its highly valuable agar oil used in the production of high grade perfumes and traditional medicines. Consequently, their population in nature is threatened greatly. Conservation of this tree species is of the main concern, however, identification of A. malaccensis from other Aquilaria sp. based on morphology is very difficult and time consuming. This study aimed to determine the genetic diversity among three selected Aquilaria sp. namely A. malaccensis, A. sinensis (Lour.) Spreng. And A. subintegra Ding Hou using random amplified polymorphic DNA (RAPD) markers and to differentiate A. malaccensis from A. sinensis and A. subintegra. Out of ten RAPD primers, four primers (G12, R15, U13 and OPA 05) produced the most clear and reproducible bands. A total of 24 bands were scored from the four primers. Construction of dendrogram resulted in two major clusters; cluster I consisted of only A. malaccensis accessions, and cluster II consisted of A. subintegra and A. sinensis accessions. This indicates that A. subintegra is more closely related to A. sinensis while A. malaccensis is genetically distant from both. Species-specific bands for A. malaccensis were produced at 875, 1000 and 2500 bp by G12 primer, and at 2500 bp by OPA 05 primer. This study laid the foundation for a creation of rapid and cost effective molecular identification of A. malaccensis.